Translation Problems Arising from Culturally Marked Translation Units in Children's Literature - Jiménez-Carra, María Nieves; Mendoza García, Inma (Routledge, 2024)
This chapter studies translation problems arising from culturally marked translation units in the genre of children's literature. First, the description and rationale of the corpus is presented, followed by the theoretical framework for the study, which is based on the following four concepts: skopos, culturally marked translation unit, acceptability and translation problem. This research builds on a previous study in which descriptive translation studies methodology was applied to a more extensive corpus. The two aims are, on the one hand, to create a grounded-theory-based categorisation of translation problems that arise from culturally marked translation units and, on the other, to determine whether the application of Grounded Theory and descriptive translation studies leads to the same or different outcomes (categorisations) in the context of the research at hand.
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/
Keywords: Literatura infantil - Traducción; Traducción; Teoría fundamentada; Translation problems; Children's literature; Culturally marked translation units; Grounded theory; Descriptive translation studies